Nebuchadnezzar's dream: the Crusades, apocalyptic prophecy, and the end of history - Rubenstein, Jay (Oxford University Press, 2019)
"In 1099, the soldiers of the First Crusade, summoned by the Pope and gathered from throughout Christendom, took Jerusalem. As the news of this victory spread throughout Medieval Europe, it felt nothing less than miraculous and dream-like, to such an extent that many believed history itself had been fundamentally altered by the event and that the Rapture was at hand. As a result of military conquest, Christians could see themselves as agents of rather than mere actors in their own salvation. The capture of Jerusalem changed everything. In Nebuchadnezzar's Dream, Jay Rubenstein maps out the steps by which the social, political, economic, and intellectual shifts occurred throughout the 12th century, drawing on those who guided and explained them. The Crusades raised the possibility of imagining the Apocalypse as more than prophecy but actual event. Rubenstein examines how those who confronted the conflict between prophecy and reality transformed the meaning and memory of the Crusades as well as their place in history"